(untitled) (Research, Society and Development, 2022)
Wheat is one of the most important cereals in the world, from which numerous food products are produced, both for human and animal food. Currently, the crop represents 30% of world production and Brazil produces annually about 6.30 million tons. However, one of the main limitations of the crop is its management and the efficient use of nitrogen in the soil, thus fertilization with fertilizers, especially nitrogen is one of the major productive costs for the crop. Thus, research seeking alternatives that provide the same or even more efficient results is becoming increasingly frequent. Thus, the objective of this research was to evaluate the effect of inoculating wheat seeds with organo-mineral and mineral fertilizers. The research was conducted in the city of Machado, in a randomized block design, in 2x2 factorial scheme, with two sources of fertilization and the presence or absence of inoculant in the seeds. The results showed no statistical difference with the physical characteristics of the plants by the type of fertilizer used, but productivity was higher when mineral fertilizer was used. In relation to the inoculant, the presence of the same provided an improvement in the productive results, but in the physical characteristics of the plants, it did not bring results. Thus, it can be concluded that the mineral fertilizer brings better results for the culture and that the presence of the inoculant brings significant gains in relation to productivity, having greater quantities of grains per ear and with greater weights.